2020
DOI: 10.33215/sjom.v3i1.263
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of Organizational Justice and Perceived Organizational and Supervisor Support on Employee’s Level of Trust?

Abstract: Aim - Past studies support the importance of organizational justice and its impact on employees' work attitudes. There are many factors that affect the employees’ work attitude but their perceptions about organizational justice and support are significant factors. Many studies have been conducted to investigate the relationship between Organizational justice and trust but there is a lack of research to measure the mediating role of perceived support. This study examines the role of perceived support as a media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As supervisors act as agents of the organization, their authenticity, empathy and support can be the main reason for nurses’ positive perceptions about organizational support, and this benefits nurses’ active learning and positive working. Similarly, Arif et al (2020) revealed that organizational justice acts as an important resource for exchange between employees and their organizations. Organizational justice can promote employees’ perceptions of sufficient care and support from their organization, which increases their willingness to put more energy into their work and learning.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As supervisors act as agents of the organization, their authenticity, empathy and support can be the main reason for nurses’ positive perceptions about organizational support, and this benefits nurses’ active learning and positive working. Similarly, Arif et al (2020) revealed that organizational justice acts as an important resource for exchange between employees and their organizations. Organizational justice can promote employees’ perceptions of sufficient care and support from their organization, which increases their willingness to put more energy into their work and learning.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, it could be explained that a positive effect of organizational justice on thriving at work is one which promotes fairness in the workplace and is perceived to be the source of trust in an organization (Nawaz et al 2018). The stronger the sense of trust and respect of employees have regarding the fairness of an organization, the easier it is to generate a feeling of vitality and learning (Arif et al 2020). Of significance is that our findings corroborated that workplace violence had an important effect on thriving at work.…”
Section: Discussionmentioning
confidence: 99%
“…According to Arnéguy et al (2021) , having fair overarching organizational justice will lead to employees having a positive perception of change, which will increase their Readiness for change. Empirical research such as ( Marzucco et al, 2014 ; Arnéguy et al, 2018 ; Hussain et al, 2019 ; Arif et al, 2020 ) has consistently demonstrated the positive influence of organizational justice on change-related reactions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…It serves Pakistan's domestic as well as its international markets, and it is a significant contributor to the country's total volume of exports. According to the Pakistan Bureau of Statistics (PBS), the power loom industry had a significant part in Pakistan's textile and garment exports, which totaled US$ 12.4 billion in the fiscal year 2020-21 (Fayaz. A., et al, 2021b.…”
Section: Introductionmentioning
confidence: 99%